Formação em saúde para o cuidado de crianças e adolescentes vítimas de violência sexual – um olhar pelo paradigma complexo. - Alves , Claudia Adão (Universidade Federal de São Carlos, 2025)
Sexual violence against children and adolescents persists as a serious public health problem in Brazil and globally. Health training to deal with this phenomenon is a challenge. The aim of this study was to understand the meanings attributed to training for the care of children and adolescents who are victims of sexual violence by undergraduates in health courses at a public university. This is a study based on the assumptions of qualitative research, anchored in the Paradigm of Complexity, carried out with sixteen undergraduate health students, eight from the Nursing course and eight from the Medicine course. Data was collected through semi- structured interviews between April and June 2024. The data was analyzed using reflective thematic analysis. Three final themes emerged: Complexity of Sexual Violence against Children and Adolescents; Complexity of Caring for Children and Adolescents Victims of Sexual Violence; and Complexity in Professional Training on Sexual Violence against Children and Adolescents. The first theme deals with the social, cultural, family and legal elements surrounding the phenomenon of violence. The second addressed the need for comprehensive, interprofessional and intersectoral care, although this is still perceived through referrals and institutionalization. The last theme looks at training, demanding complex skills that assume family dialog as both protection and risk. Caring for children and adolescents who are victims of sexual violence must encompass the developmental singularities and intersectionalities present. In this sense, the biggest challenge is family- centered care versus managing violence in the family context. The meanings attributed to training for this care involved weaving a cross-cutting process that delves deeper into the subject, using active and participatory strategies, with a focus on the students. The perspective taken here is innovative and can support the design of curricula, as well as curricular reformulations, considering the current challenges for nursing and health care.
Health education for the care of children and adolescents who are victims of sexual violence – a perspective through the complex paradigm.
Keywords: Violência sexual; Violência infantil; Família; Ensino; Formação em enfermagem; Formação médica; Sexual violence; Child abuse; Family; Teaching; Education; Nursing; Medical; CIENCIAS DA SAUDE